Regulation of transglutaminase activity in articular chondrocytes through thrombin receptor-mediated factor XIII synthesis - Rosenthal, Ann K.; Mosesson, Michael W.; Gohr, Claudia M.; Masuda, Ikuko; Heinkel, David; Seibenlist, Kevin R. (Thrombosis and Haemostasis, 2004)
Transglutaminases are a family of enzymes that catalyze the formation of ɛ-(γ-glutamyl)lysine isopeptide bonds in proteins, an activity that has been implicated in the pathogenesis of cartilage matrix mineralization in degenerative arthritis. Type II transglutaminase and thrombin-activatable factor XIII have been identified in articular cartilage. Thrombin, a coagulation protease, is found in pathological synovial fluids, and is known to stimulate transglutaminase activity in non-articular tissues. We investigated the effects of thrombin on transglutaminase activity in porcine articular chondrocytes. Direct addition of thrombin to chondrocyte lysates resulted in increased transglutaminase activity due to proteolytic conversion of factor XIII to XIIIa. Thrombin-treated chondrocyte cultures (0.001 to 2.0U/ml) also showed increased transglutaminase activity. Thrombin treatment of chondrocyte cultures increased transglutaminase activity as early as 15 minutes after addition, an effect that we attributed to factor XIII activation. Additional stimulatory effects of thrombin were observed in cultured chondrocytes at 4 and 24 hours. A thrombin receptor agonist peptide (TRAP) which activates the PAR1 thrombin receptor mimicked these later effects. Thrombin treatment of chondrocyte cultures increased factor XIII mRNA and protein levels, without affecting levels of type II transglutaminase. Thus, thrombin stimulates transglutaminase activity in articular cartilage by directly cleaving factor XIII and by receptor-mediated upregulation of factor XIII synthesis. Such increases in potential transglutaminase activity may facilitate pathological matrix calcification in degenerative arthritis.
Keywords: Degenerative arthritis; calcium pyrophosphate crystals; mineralization; proteases; articular cartilage